GAMBARAN TINGKAT KEPATUHAN PENGOBATAN HIPERTENSI PADA LANSIA DI PUSKESMAS I DENPASAR TIMUR - Anom Swari, I Gusti Ayu Anom Swari I Gusti Ayu (Universitas Udayana, 2022)
Background: Hypertension is a condition where blood pressure increases in patients, which usually occurs in elderly patients. According to several aspects, one of which affects the quality of life of people with hypertension is adherence to treatment. The purpose of this study was to describe the level of adherence to hypertension treatment in the elderly at Puskesmas I East Denpasar. This study used a cross-sectional descriptive design at Puskesmas I, East Denpasar. The research sample used was all elderly people who suffered from hypertension and had been diagnosed with hypertension and had undergone hypertension treatment at Puskesmas I East Denpasar. The sampling technique used is convenience sampling with a minimum of 32 samples. The research instrument used was the MMS-8 questionnaire and a questionnaire made by the researcher himself. The collected data will be processed descriptively with SPSS. Most of the respondents did not comply with hypertension treatment. Most of the obedient respondents were male (33.3%), education level graduated from elementary school (50%), civil servant occupation (100%), marital status (29.6%), no other diseases (30, 8%), taking medication >3 months (33.3%), taking 1 to 2 types of medicine (30.8%), not receiving family support (50%), having support from health workers (28.6%), the score of knowledge level about hypertension and its treatment is >4 (30.4%), and easy access to services (44.4%). can be concluded in this study that respondents have a low of compliance. Keywords: Compliance, Treatment, Hypertension, Elderly